A working memory intervention for HIV positive children and adolescents - Fraser, Shona (My University, 2018)
It is well known tha HIV causes a progressive encephalopathy in the immature brain and preferentially disrupted myelination in the fronto-cortical circuits. This significantly impacts executive functioning, of which working memory Is a component. Antiretroviral treatment is unable to reverse these effects, providing a compelling rationale alternative interventions for neurocognitive disability in adolescent HIV infection. Emerging research has investigated the role of cognitive training interventions in remediating working memory difficulties in children and adolescents with neurodevelopmental disorders, such as Attention Disorders, Dyslexia, and Specific Language Impairement. Such interventions depend largely on the concept of neural plasticity and the subsequent extent to which a child or adolescent's brain is plastic and can change through cognitive stimulation.
Keywords: HIV; Adolescent; Adult Children